MINAT BELAJAR MATEMATIKA DALAM PERMAINAN TRADISIONAL ENGKLEK - Dinda Kusuma Wardani; M. Syaffrudin Kuryanto; Lovika Ardana Riswari (Universitas Insan Budi Utomo, 2024)
This research aims to find out the level of student interest in learning the traditional game of engklek in the context of mathematics learning. This research used a qualitative approach and was conducted in Kropak Village, Winong District, Pati Regency. The research subjects consisted of the homeroom teacher and several class V students at SDN Kropak 02. The data collection methods applied included observation, interviews and documentation. Data analysis uses techniques introduced by Miles and Huberman, namely data reduction, data collection, and drawing conclusions. This research focuses on four students out of a total of 20 students in the class. The four students who were research subjects had the initials AA, RR, SW, and PLC, which previously indicated a lack of interest in mathematics subjects. Through observations of student responses and the results of interviews with teachers, it can be concluded that the integration of the traditional engklek game in the learning process is able to generate interest in learning and student involvement. Findings from the research show an increase in student interest in learning, reflected in the high level of student enthusiasm during the learning process. They seemed more enthusiastic and active in participating in learning activities and showed greater interest in the material being taught.